Tetralogy of Fallot: Pushing Through Despite Long Odds - Han, Frank (JACC Case Rep, 2019)
The natural history of tetralogy of Fallot depends on whether a transannular pulmonary valve patch or shunt surgery was necessary in infancy. This case illustrates the feasibility of cardiac rest on extracorporeal membranous oxygenation for a very ill adult with conduit endocarditis who received a right ventricle–to–pulmonary artery valveless conduit for later transcatheter pulmonary valve replacement. (Level of Difficulty: Advanced.)